Lorne : the man who invented Saturday Night Live - Morrison, Susan, 1959 or 1960- (Random House, 2025)
"Ever since its debut in the fall of 1975, Saturday Night Live's impact on the culture has been lasting and profound. It has been a breeding ground for our brightest comedy stars, launching the careers of John Belushi, Gilda Radner, Bill Murray, Eddie Murphy, Adam Sandler, Will Ferrell, Tina Fey, Amy Poehler, Pete Davidson, and many many more. Its iconic sketches--from Wayne's World to Weekend Update to Coneheads to the Californians to of course, More Cowbell--have dominated water cooler talk for five decades, and its catchphrases, from "we're not worthy!" to ""Daaaaa Beeeears" are embedded in the public lexicon. And at the center of it all, from the moment of its inception to the present day, is one man: producer Lorne Michaels. Over his 50 years running the show, Lorne Michaels has become a revered, inimitable and bewildering presence in the world of entertainment. He's a mogul, a kingmaker, a tastemaker, a grudge-holder, a mensch, a workaholic, a genius spotter of talent, a ruthless businessman, a name dropper, an obsessive step counter, the inspiration for Dr. Evil, a winner of 90 Emmys--and a mystery. Generations of writers, actors, and stars have spent their lives trying to figure him out. He's "Obi wan Kenobi" (Tracey Morgan), the "Great and Powerful Oz" (Kate McKinnon), the Godfather (Will Forte), or "some kind of very distant, strange Comedy God" (Bob Odenkirk). Lorne will introduce you to him, in full, for the first time. With unprecedented access to Michaels (who has spent his career mostly avoiding reporters) and the entire SNL apparatus, The New Yorker's Susan Morrison takes you behind the curtain for the rollicking, definitive story of how Lorne created the institution that would change comedy forever. Lorne features hundreds of interviews with Michaels, conducted over several years; his close friends (such as Paul Simon, Paul McCartney, and Steve Martin); and the candid, hilarious stars of the show, including Chris Rock, Amy Poehler, Jason Sudeikis, Bill Hader, Buck Henry, Chevy Chase, and more. Nearly a decade in the making, Lorne is an intimate, deeply reported, and wildly entertaining account of a man singularly obsessed with the show that would define his life--and change American culture"--